Ur in the twenty-first century CE proceedings of the 62nd Rencontre assyriologique internationale at Philadelphia, July 11-15, 2016 - Frame, Grant; Jeffers, Joshua, 1977-; Pittman, Holly (Eisenbrauns, 2021)
The city of Ur--now modern Tell el-Muqayyar in southern Iraq, also called Ur of the Chaldees in the Bible--was one of the most important Sumerian cities in Mesopotamia during the Early Dynastic Period in the first half of the third millennium BCE. The city is known for its impressive wealth and artistic achievements, evidenced by the richly decorated objects found in the so-called Royal Cemetery, which was excavated by the British Museum and the University of Pennsylvania from 1922 until 1934. Ur was also the cult center of the moon god, and during the twenty-first century BCE, it was the capital of southern Mesopotamia.With contributions from both established and rising Assyriologists from ten countries and edited by three leading scholars of Assyriology, this volume presents thirty-two essays based on papers delivered at the 62nd Rencontre Assyriologique Internationale held in Philadelphia in 2016. Reflecting on the theme "Ur in the Twenty-First Century CE," the chapters deal with archaeological, artistic, cultural, economic, historical, and textual matters connected to the ancient city of Ur. Three of the chapters are based on plenary lectures by senior scholars Richard Zettler, Jonathan Taylor, and Katrien De Graef. The remainder of the essays, arranged alphabetically by author, highlight innovative new directions for research and represent a diverse array of topics related to Ur in various periods of Mesopotamian history. Tightly focused in theme, yet broad in scope, this collection will be of interest to Assyriologists and archaeologists working on Iraq.